Technology structure and skill Structure: costly investment and complementarity effects quantification. - Sochirca, Elena (2014)
Based on an extended model of endogenous directed technical change and on cross-country data, we identify and quantify the long-run link between: (i) the technology structure (high- versus low-tech sectors) and the skill structure (high- versus low-skilled workers), by considering an explicit role for the (potential) com- plementarity between technological goods; (ii) the Tobin-q and the technology characteristics of the rms through their impact on economic growth. Our es- timation and calibration exercise suggests the existence of a moderate degree of complementarity and of an elastic relationship between the Tobin-q and key tech- nology parameters.